Measuring the Impact of Financial Liberalization at Turnover Rates on Commercial Banks’ Profitability - Husam Tareq Jasim; Dr. Anis Bouabid (Migration Letters, 2023)
The study aimed to measure the long-term impact of financial liberalization at turnover rates at banks’ profitability levels of local private commercial banks listed on the Iraqi stock exchange, and to achieve this, the study relied on unbalanced longitudinal data of 22 banks during the period (2009-2020) with a total of 236 annual observations. The study used four rates to express turnover rates and they are as follows: Asset turnover, creditors, debtors, and working capital. While using the rate of return on assets (ROA) to express the level of profitability. A Positive impact of asset turnover was found and Working capital on return on assets by using one-way fixed effects method and Dynamic panel data method. While creditors’ turnover relationship to profitability was non-linear, taking the form of a U. In other words, the effect of creditors’ turnover is negative on profitability when creditors’ turnover rates are low. However, this effect turns positive at high creditor turnover rates. On the other hand, debtors’ turnover had no significant effect on profitability. The results also confirmed that these relationships are consistent and strong against different assessment methodologies. These results thus give support to bank management and policymakers to take into account its strategic plans and directions to achieve a higher goal of profitability.